Pengaruh Aksebilitas Dan Fasilitas Pasar Terhadap Pendapatan Pedagang Di Pasar Pada Lewoleba - Redempta Sewai B. K. Sulaona; Fransina W. Ballo; Maria I. Hewe Tiwu (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to explain the influence of accessibility and facilities on traders' income at Pada Lewoleba Market. This research is quantitative research with the data used obtained from the results of a questionnaire distributed to 75 respondents. The analytical method used is instrument testing and multiple linear regression which is processed using Eviews 12 software. The results of this study show that partially the accessibility variable influences the income of traders in the market on Lewoleba and the facility variable influences the income of traders in the market on Lewoleba, this is due to renovations carried out in stages by the Lembata Regency Regional Government which are continuously being improved. Simultaneously, the variables of accessibility and facilities influence the income of traders in the market on Lewoleba